(untitled) (Eurasian Research Bulletin, 2023)
Kayumova N.A., Fayziyeva Sh.F. Kompyuter tarmoqlari modellarini yaratuvchi dasturlardan foydalanish. https://cajecs.com/index.php/cajecs/ar ticle/ view/26/v1i28 2. Каюмова Н. А., Суропов Б. М. ПСИХОЛОГО-ПЕДАГОГИЧЕСКИЕ АСПЕКТЫ В ПРОЦЕССЕ ОБУЧЕНИЯ ИНФОРМАЦИОННОКОММУНИКАЦИОННЫ ТЕХНОЛОГИИ //Интернаука. –2019. – №. 28. – С. 66- 67. 3. NA Kayumova, BM Suropov. Improvement of the methodological system for training computer tea chers based on the integration approach. https://www.cibgp.com/article_9883.ht ml 4. КАЮМОВА Н. А. THE NEW TECHNOLOGIES IN THE ORGANIZATION OF THE ELECTRONIC LEARNING ENVIRONMENT IN HIGHER EDUCATION //Современное образование(Узбекистан). –2021. – №. 2. – С. 64-73. 5. Каюмова Н. А. ОЛИЙ ТАЪЛИМДА ЭЛЕКТРОН ТАЪЛИМ МУҲИТИНИ ТАШКИЛ ЭТИШДА ЯНГИ ТЕХНОЛОГИЯЛАР //Современное образование (Узбекистан). –2021. – №. 2 (99). – С. 64-73.